A rare case of non-functioning parathyroid carcinoma masquerading as euthyroid neck mass - Shanmugam, Subasri; Sivashankaran, Gopinathan; Valliappan, Valliammai; Elangovan, Sri Nandhini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Parathyroid carcinoma is an exceptionally rare endocrine malignancy, often functional, manifesting with hypercalcemia and elevated parathyroid hormone (PTH) levels. Non-functional parathyroid carcinoma lacks classical biochemical features, making its diagnosis particularly challenging. Here, we present a case of 60-year-old male with swelling in the anterior aspect of right side of neck. Ultrasound of the neck showed complex cystic nodule suggesting fine needle aspiration cytology (FNAC) to rule out papillary neoplasm. FNAC results were suggestive of hyperplastic colloid nodule. Then the routine blood tests, including serum calcium and thyroid function, were within normal limits and the patient was taken up for total thyroidectomy. Histopathology of the specimen revealed features suggestive of medullary thyroid carcinoma, necessitating IHC. Tumor cells stained strongly positive for GATA3 and PTH, while being negative for calcitonin, MCEA, TTF1, and S100. Focal capsular and lymphovascular invasion was noted and the final diagnosis of parathyroid carcinoma was made. Parathyroid carcinoma is a rare and aggressive tumor that may clinically and radiologically mimic a thyroid nodule, especially in its non-functional form. Diagnosis is extremely difficult and is best confirmed with immunohistochemistry.